FACTORS INFLUENCING ATTITUTES AND INTENTIONS TO PURCHASE SUNSCREEN PRODUCTS AMONG MALE MINE WORKERS IN INDONESIA - Prabowo, Agus Dhodhy; Winartio, Cory; Widagdo, Gregorius Gatot; Amalia, Putri; Dumila, Ratna; Istijanto (Fakultas Ekonomi dan Bisnis Universitas Pancasila Jakarta, 2026)
Male mine workers are the group with the highest exposure to ultraviolet (UV) radiation and face significant risks of skin damage, including : sunburn, hyperpigmentation, premature aging, and even skin cancer. However, sunscreen use in this group remains very low due to the perception that sunscreen is not important, impractical, or unsuitable for the work environment. This study aims to analyze the factors that influence attitudes and purchase intentions regarding sunscreen among male mine workers in Indonesia by integrating the Theory of Reasoned Action (TRA) and the Technology Acceptance Model (TAM), while also adding the Perceived Behavioral Control variable from the Theory of Planned Behavior (TPB) framework. This research examines the effects of Health Care, Perceived Physical Benefits, Aging Effect Benefit, Subjective Norm, Perceived Ease of Use, Perceived Risk, and Perceived Behavioral Control on Attitude Toward Behavior and Purchase Intention regarding sunscreen use. The research method uses a quantitative survey approach with purposive sampling techniques targeting male mine workers in various open-pit mining locations across Indonesia. Data are analyzed using a correlational approach to examine relationships between variables according to the theoretical model. The results are expected to provide a comprehensive understanding of the psychological, social, and perceptual factors that determine skin protection behavior among mine workers. The findings of this study contribute to the development of health behavior adoption theory in the context of workers in open environments and provide practical recommendations for mining companies, particularly the Health and Safety Department, in designing interventions to increase sunscreen use as part of a safety culture.